Struktura pytań - Jonkisz, Adam (Filozofia Nauki, 2020)
By drawing on the results presented in (Jonkisz 2019), this paper formulates a general schema of questions. The schema is then applied to specific kinds of questions (with examples). The paper defines some auxiliary concepts, including a broader notion of negation, which are then employed in the analysis of the structure of questions. The accuracy of the proposed schemata has been checked in the case of some examples regarded in the literature as difficult to analyze and classify.